Dual Effect of ITO‐Interlayer on Inverted Top‐Illuminated Polymer Solar Cells: Wetting of Polyelectrolyte and Tuning of Cavity. (23rd May 2016) - Dong, Wan Jae; Park, Jae Yong; Ham, Juyoung; Jung, Gwan Ho; Lee, Illhwan; Lee, Jong‐Lam
Abstract : Flexible inverted top‐illuminated polymer solar cells (IT‐PSCs) are fabricated by wetting of polyelectrolyte and designing a microcavity structure by laying an indium‐tin‐oxide (ITO) interlayer on top of an Ag reflector. The ITO‐coated Ag makes the surface hydrophilic, thereby improving wettability of polyethyleneimine (PEIE). This increased wettability of PEIE yields a reflective cathode with low work function of 3.73 eV. The ITO layer also tunes the light absorption spectrum in the active layer. Finite‐domain time‐difference simulation provides evidence that the ITO layer played a role in both the shift in resonant wavelength in the microcavity and confinement of the electric field to the active layer. Time‐dependent simulation suggests that the time to reach steady‐state light absorption is longer (6.6 fs) when a microcavity is present than when it is not present (3.8 fs); i.e., the microcavity increases light absorption in the active layer. The designed IT‐PSCs show a maximum photo‐conversion efficiency of 6.4% on plastic film and 6.1% on opaque copper foil; these are the highest values obtained by top‐illuminated PSCs on a metallic substrate. The IT‐PSCs have excellent mechanical flexibility and more stable in air than conventional normal structured devices. Abstract : Flexible inverted top‐illuminated polymer solar cells (IT‐PSCs) are fabricated on metallic substrate by designing a microcavity structure. The ITO layer allows the wetting of cathode interlayer of polyelectrolyte on Ag reflector. The spectral tuning of absorption spectrum is simultaneously demonstrated by employing the ITO interlayer. The optimized IT‐PSCs shows high‐efficiency, excellent mechanical flexibility, and air‐stability.